2016
DOI: 10.1177/0003702816667516
|View full text |Cite
|
Sign up to set email alerts
|

Optical Screening of Female Breast Cancer from Whole Blood Using Raman Spectroscopy

Abstract: This study is intended to develop a screening method for female breast cancer (BRC) from whole blood using Raman spectroscopy. A multivariate partial least squares (PLS) regression model is developed which is based upon Raman spectra of BRC-positive and healthy participants. It yields coefficients of regression at the corresponding Raman shifts. These coefficients represent the changes in molecular structures which are associated with the progress of disease. The present study pointed out some specific molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…This raises the possibility of utilising Raman analysis as a non-invasive, clinical imaging technique to identify calcifications likely to be representative of a malignancy. A recent study even found that Raman analysis of whole blood samples could detect Raman shifts characteristic of calcium oxalate and hydroxyapatite, which were elevated in blood from breast cancer patients (42).…”
Section: Chemical Composition Of Microcalcificationsmentioning
confidence: 99%
“…This raises the possibility of utilising Raman analysis as a non-invasive, clinical imaging technique to identify calcifications likely to be representative of a malignancy. A recent study even found that Raman analysis of whole blood samples could detect Raman shifts characteristic of calcium oxalate and hydroxyapatite, which were elevated in blood from breast cancer patients (42).…”
Section: Chemical Composition Of Microcalcificationsmentioning
confidence: 99%
“…Several reports have shown that spontaneous Raman or SERS analysis of liquid or dried blood serum/plasma can efficiently discriminate between control and several types of cancer such as breast,2123 lung,24 ovarian,25 colorectal,2628 or head and neck cancer 29. In spite of that, the results of these preliminary studies cannot be compared directly, because of significant differences in the experimental setup employed for acquiring the SERS spectra of serum.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, all the patients of the stage 4 are found very much distinct from each other, indicated by the clustering pattern of the Raman spectral data of this stage in the PCA scatter plots (Figure 5 a and Figure 6a) which may be due to the increase in the degree of the severity of the breast cancer, and the diversity of routes towards metastasis. This study advances previously published work related to the use of Raman spectroscopy for the characterization/diagnosis of breast cancer by using blood plasma/serum samples from clinically diagnosed patients, as the spectral markers of689 (Nucleotide conformation), 788 (phosphodiester bands in DNA), 828 (tyrosine/protein), 848 (most probably due to single bond stretching vibrations for amino acids and polysaccharides) and 1663 cm -1 (DNA) have not previously been identified.In these reports, Bilal et al applied Partial least squares(PLS) regression analysis to the Raman spectral data acquired from blood serum of breast cancer and healthy individuals and coefficients of regression were determinedwith sensitivity of 90% and specificity 75% which are associated with the changes at the bio-molecular level[23], while in the current study sensitivity and specificity have been found to be as high as 100% in the comparison of control and breast cancer samples. In another study, Pichardo-Molina et al applied Raman spectroscopy along with principal components analysis (PCA) and PCA-Linear Discriminate Analysis (LDA) to breast cancer and control blood samples, identifying specific bands which distinguish breast cancer blood serum samples from the healthy ones[24].…”
mentioning
confidence: 82%
“…applied Partial least squares(PLS) regression analysis to the Raman spectral data acquired from blood serum of breast cancer and healthy individuals and coefficients of regression were determined which are associated with the changes at the bio-molecular level, hence indicating the development of the disease [23]. In another study, Pichardo-Molina et al applied Raman spectroscopy along with principal components analysis (PCA) and PCA-Linear Discriminate Analysis (LDA) to breast cancer and control blood samples, identifying specific bands which distinguish breast cancer blood serum samples from the healthy ones [24].…”
Section: Introductionmentioning
confidence: 99%